ANTIFUNGAL ACTIVITY OF SIAM CITRUS (Citrus nobilis L.) ESSENTIAL OIL AGAINTS Lasiodiplodia theobromae THE PATHOGEN OF BLENDOK DISEASE - Pranata, Kadek Dwipayana; Wirawan, I Gede Putu; Wibawa, I Putu Agus Hendra; Suada, I Ketut; Wijaya, I Nyoman; Phabiola, Trisna Agung (International Journal of Biosciences and Biotechnology; Vol 11 No 2 (2024): International Journal of Biosciences and Biotechnology, 2024)
Siam citrus ( C. nobilis L.) is a type of citrus that is most widely cultivated in Bangli Regency. The main disease that attacks citrus plants is blendok caused by the fungus L. theobromae . Based on research siam citrus peel contains essensial oils that have potential as antifungals. The aim of this study was to study chemical content of essensial oil from siam citrus peel and its activity as an antifungal againts L. theobromae . Essensial oil was destilled using hydro steam distillition and analyzed by means of GC-MS. Antifungal activiy testing was carried out using the agar-well diffusion method with concentrations of 1%, 10%, 25%, 50%, 75%, and 100%. Dithane M45 6 g/l and DMSO 10% were used as positive and negative controls. The results showed that the siam citrus peel from Kintamani, Bangli contains essensial oils with the main chemical components, i.e. D-limonene (57.26%), Beta-pinene (9.09%), and Beta-myrcene (4.03%) which has uses as an antifungal, additive, antitumor, asthma and allergy reliever, repellent, anti-inflammatory, antioxidant, anticancer, and antibacterial. Essential oil concentration of 25 to 100% can inhibit the growth of L. theobromae . The largest diameter of inhibition is shown at a concentration of 100% and the smallest diameter of inhibition is shown at a concentration of 25%. Keywords : C. nobilis L., essensial oils, GC-MS, L. Theobromae, antifungal